AUTOMATED EDITING TOOLS FOR MEDIA STUDENTS: A COMPARATIVE STUDY - Jadhav, Ragini Kunal; Shalini E; Kurulekar, Mahesh; Goel, Pooja; Bhat, Urvashi; Upadhyay, Manisha (ShodhKosh: Journal of Visual and Performing Arts, 2026)
Purpose: To assess automated editing tools applied in the media education on the basis of technical and pedagogical terms. Methodology: Four categories of automated editing tools were evaluated based on a multi-dimensional model based on the level of automation, usability, creative control, pedagogical compatibility, and workflow efficiency. A student case study based on tasks was added to quantitative scoring. Results: The results show that high automation is more efficient and accessible, yet less creative transparency and conceptual comprehension. Equipment with balanced automation has better learning results. Implications: The study suggest that an automated editing tool should be integrated in the media education stages on the basis of a blended approach, depending on the stage. Originality: The article offers a comparative educational theory of evaluating AI-assisted editing tools.